2018
DOI: 10.33086/jhs.v8i1.224
|View full text |Cite
|
Sign up to set email alerts
|

Peran Keluarga Dalam Peningkatan Kemampuan Interaksi Sosial Bermasyarakat Klien Skizofrenia Pasca Perawatan Di Rumah Sakit

Abstract: Family has a strategic function for the schizophrenic client’s social interaction, the role of family really needs to reached client independent, The role of family enables the schizophrenic individual to re-adapt the social life in the society. This research destination to analyze realiontship the family role and the Scizophrenic client’s interaction level in the social life. This research applied the analytic cross sectional design. The populations of the research were the schizophrenic clients who have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Interaksi sosial bermasyarakat bagi penderita dapat membantu dalam meningkatkan hubungan sosial di lingkungan sekitar rumah sehingga bisa memunculkan stigma yang positif bagi penderita 29 .…”
Section: Koping Keluarga Terhadap Stigma Sosialunclassified
“…Interaksi sosial bermasyarakat bagi penderita dapat membantu dalam meningkatkan hubungan sosial di lingkungan sekitar rumah sehingga bisa memunculkan stigma yang positif bagi penderita 29 .…”
Section: Koping Keluarga Terhadap Stigma Sosialunclassified
“…Supports from family members are important for individuals suffering from mental disorders, aiming at fulfilling the patients' independence, adaptation to the environment around the patients, the smooth process of treatment, and social interaction. The results showed that there was a significant relationship between the role of family members and the increase of social interaction in social conditions among psychiatric patients (Maghfiroh & Khamida, 2015). For this reason, researchers suggest that there is a need for family involvement in treating patients and the need to apply family therapy to each schizophrenic patient.…”
Section: Introductionmentioning
confidence: 99%